Managing knowledge flows within open innovation: knowledge sharing and absorption mechanisms in collaborative innovation - Tutuk Ari Arsanti; Neil Rupidara; Tanya Bondarouk (Cogent Business & Management, 2024)
This paper aims to explore the bottom-up emergence of inter-organizational knowledge flow mechanisms within collaborative innovation processes in the research-based organizations, including universities and companies. The knowledge flow mechanism in collaborative innovation is viewed from the process of knowledge sharing and absorption. The data is primarily based on interviews with representatives of the case organizations involved in open innovation projects, who also act as actors in the collaborative innovation processes. This research discovers and provides insights into the mechanisms used in knowledge sharing and absorption. It also posits the role of actors as `intermediaries' in the process of cross-organizational team interaction in managing knowledge flows.This study aims to explore the bottom-up emergence of inter-organizational knowledge flow mechanisms within collaborative innovation processes in the research-based organizations, including universities and companies. The knowledge flow mechanism in collaborative innovation is viewed from the process of knowledge sharing and absorption. By conducting in-depth interview, our findings highlight the importance of mechanisms that used in knowledge sharing and absorption. In addition, our findings are also show the intermediaries role of actors in the process of cross-organizational team interaction in managing knowledge flows. The results offer significant perspectives for managers overseeing collaborative innovation initiatives, especially those that operate in cross-border or cross-cultural contexts with suppliers, partners, or other external entities.
Keywords: O15; O3; O36; 650; Open innovation; collaborative innovation; knowledge flow; knowledge sharing; absorptive capacity